Accounting and post-colonial resistance: Affective ambivalence in the international development assemblage - Duenas, Nelson (Accounting, Organizations and Society, 2025)
This paper is concerned with the understanding of resistance in accounting research. Using the case of a Southern Non-Governmental Organization (NGO) and its relationships with donors within the international development assemblage, I discuss how the organization, in experiencing mixed feelings towards its donors' managerial discourses and accounting practices, engages in a process of resistance. Such resistance operates amidst a processual interplay of attraction and repulsion towards the colonial opposite. Using Homi Bhabha's Postcolonial Theory (PCT) and its emphasis on the affective dimension in colonial encounters, I find that the NGO's actions are nestled within hybridity and ambivalence, which drive the NGO towards balancing opposing forces to move forward in the assemblage. I contribute to accounting literature by offering an affective understanding of the ambivalence produced by postcolonial relations mediated by accounting, and by reconceptualizing resistance in accounting research as a flux of affects with political implications in shifting relationships.